Gestão escolar e inclusão : os desafios da direção na rede privada de ensino - Vieira, Maria Angélica Cardoso (2019)
The current educational demands demonstrate the need for changes in the school to meet the students according to their singularities and specificities, that is, a school that embraces diversity and continue to improve its processes to reach a level of excellence. The role of the school principal is key to managing these changes, since he is the majority manager in the school environment. This research project will aim to characterize the challenges of school management in promoting inclusive processes in a private school network. For the construction of this project, a bibliographical review was undertaken, contemplating theoretical axes and researches about the discussion about the diversity in the school environment, resources used in the construction of a school in an inclusive perspective, as well as the actions of the school director as promoter of inclusive processes. Two distinct, but complementary, methodological steps were proposed. The first was a quantitative nature, in view of the fact that it sought to describe, through a questionnaire, the beliefs of 33 directors. In a second moment of the study, a qualitative approach was used, to deepen the same previous questions, but through application of interview with three directors. It was possible to identify, through these instruments, that principals believe that Inclusive Education is necessary and important, but they pointed out some difficulties for implementation, especially regarding the formation of the teaching and support group, including families that are often not school partners for the development of the student with a disability, denying or neglecting counseling to this student and finally mentioning the lack of governmental or institutional support for inclusive issues to be in a more advanced process in the school space where they are currently. Directors have shown that they believe in the importance of supporting inclusive actions, even though the processes pointed out by them, are still evolving, through actions developed by the management group, where the role of the director is central, valuing inclusive issues and directing the community school in order to encourage the reception of the diverse, valuing their potential and respecting their specificities.